Hubungan Produksi Susu Berdasarkan Grade MPPA dengan Performa Reproduksi - Komala, I.; Arifiantini, I.; Tumbelaka, L. I. T. A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
The aim of this study was to determine the potential effect of milk production based on Most Probability Producing Ability (MPPA) on reproductive performance. The secondary data of body condition score (BCS), reproductive traits and milk production were collected from Baturraden Breeding Center. Identification of FSH sub unit beta Gene polymorphisms were conducted by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) method. Milk production data was analyzed with formula repeatability (r), heritability (h) and Most Probable Producing Ability (MPPA). The data were also analyzed using correlation and ANOVA (GLM). The results showed that repeatability and heritability of milk production values were 0,84 and 0,4. Gen FSH sub-unit beta was monomorphic fixed to AB genotype and had no effect on the ability of milk production and reproductive performance. BCS values had been affected significantly   on milk production based on grade of MPPA. The correlation analysis showed that the BCS had a sizable effect on milk production with a value of r = 0,68. The relationship between BCS with milk production was expressed in the regression equation MPPA (Kg) = - 59 + 1991 BCS, means the rise of unit will increase milk production of 1991 kg/lactation.